Rancang Bangun Pengamatan pH Air Menggunakan Protokol MQTT - Cahyo Karya Basuki; Dany Primanita Kartikasari; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Water pH is the most important aspect in the field of fisheries, especially in fish cultivation in ponds. PH monitoring problems, currently very much talked about one of them is weather changes that make the management sometimes forget or are lazy to check. So that the role of technology is needed that can help overcome the problem, to convey water pH data to managers remotely. IoT or the Internet of Things is a technology concept whose application can be used to help overcome these problems, where the system works is to connect physical objects with internet communication. IoT requires a protocol to run data transmission that functions as data transport from sensors to users on a network. The protocol used is MQTT (Message Queuing Telemetry Transport) where the protocol is expected to work in low bandwidth and unrealiable networks. The mechanism applied to the system used is publish-subscribe. With a sensor node on Arduino microcontroller as a publisher. Then the Raspberry Pi microcomputer is a server that functions as a broker, time control middleware and data storage. Subscriber as the data requester adopts from java language as a simple interface to the user so that it is easy to read. From the implementation that has been made, it is obtained the results of system testing that matches expectations and obtains protocol kinerja protokolnce which refers to the average latency and delay values ​​below 1 ms, which are 0.31 ms and 0.71 ms with a test time of 3x24 hours.